2013
DOI: 10.1016/j.jmig.2013.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Pain in Gynecologic Surgeons

Abstract: Objective To describe the prevalence of musculoskeletal pain and symptoms in gynecologic surgeons. Design Prospective cross-sectional survey study (Canadian Task Force classification II-2). Setting Virtual. All study participants were contacted and participated via electronic means. Participants Gynecologic surgeons. Interventions An anonymous, web-based survey was distributed to gynecologic surgeons via electronic newsletters and direct E-mail. Measurements and Main Results There were 495 respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 16 publications
2
55
1
8
Order By: Relevance
“…[2] In our study, the rate of physical symptoms was 30 percentage points higher among female surgeons than among their male counterparts, and female surgeons had an odds ratio of 4.2 for physical symptoms compared to their male counterparts. Numbness, pain, stiffness, and fatigue were all reported at significantly higher rates by female surgeons.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[2] In our study, the rate of physical symptoms was 30 percentage points higher among female surgeons than among their male counterparts, and female surgeons had an odds ratio of 4.2 for physical symptoms compared to their male counterparts. Numbness, pain, stiffness, and fatigue were all reported at significantly higher rates by female surgeons.…”
Section: Discussionmentioning
confidence: 65%
“…Within gynecology, physician pain and related symptoms have been found to be correlated with surgeon characteristics, including height, young age, female sex, and high body mass index [1]. Female sex has also been found to as much as double the risk of surgeon discomfort associated with minimally invasive surgery [2]. Much of the physical discomfort experienced by surgeons performing minimally invasive surgery has been attributed to ergonomic challenges faced in the operating room, such as challenges due to instrument design and room set-up [4].…”
Section: Introductionmentioning
confidence: 99%
“…In a smaller study of 55 laparoscopic surgeons, 73% reported physical complaints mainly involving neck, lower back, shoulders, and thumbs during or after CL procedures . A recent survey of 495 gynecological surgeons confirmed these findings and the risk of musculoskeletal symptoms seems to be significantly higher among female surgeons . Laparoscopic pelvic surgery is especially troublesome, because the surgeon is forced to work aside the working axis, resulting in unnatural strain of arms, shoulders, back and legs .…”
Section: Resultsmentioning
confidence: 97%
“…Recent studies have reported that vaginal surgeons have a high prevalence of musculoskeletal discomfort (Adams, Hacker, McKinney, Elkadry, & Rosenblatt, 2013;Kim-Fine, Occhino, & Gebhart, 2013), which exceeds comparable prevalence estimates of musculoskeletal discomfort experienced by other surgeons and doctors (Oude-Hengel, Visser, & Sluiter, 2011). One study indicated that a majority (86.7%) of vaginal surgeons experienced pain in their neck, back, and lower extremities at least once a week (Kim-Fine, Occhino, & Gebhart, 2013).…”
Section: The Need To Assess the Postural Requirements Of Performing Vmentioning
confidence: 85%